TOWARDS TWIN TRANSFORMATIONS AND SPACES – Convoluted Conversations on the Green and Digital Futures of Work - Heinonen, Sirkka; Maree, Burgert; Sivonen, Risto; Toivonen, Saija; Viitamäki, Riku; Pättikangas, Paula (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2023)
This publication is a co-created compilation of various conversations concerning our possibilities and pathways towards futures of work. A series of interviews conducted so far within the T-Winning Spaces 2035 project have been documented here to give food for thinking and discussions concerning transformations of work and spaces. The questions of the interviews were tailor-made to address the expertise of each interviewee, while the core of the interviews touches upon the exuberant topic of futures of work in its all dimensions as well as the issues of forward-looking thinking and action. Within the interviews we also addressed the topics of creeping crises and paradoxes as regards futures of work. Altogether eight interviews were made, many of them during the International Conference organized by Finland Futures Research Centre in Turku in June 2023, plus some interviews conducted after that. The interviews are documented here as entities for readers to grasp the whole interviewing contexts, where-from thematic analyses will follow in the next phases of the project to provide narratives of future work and workspaces.